1996
DOI: 10.1007/bf02197551
|View full text |Cite
|
Sign up to set email alerts
|

Messung der aktuellen Pulpadurchblutung nach orthodontischer Kraftapplikation

Abstract: The purpose of the present investigation was to measure the effect of tooth intrusion and extrusion on pulpal blood flow in man. The flow changes were measured in 10 lateral incisors (6 subjects) by means of laser Doppler flowmetry (Perimed, Sweden) applied on the buccal surface through metal tubes bonded to the teeth. Brackets were bonded onto teeth 13 and 23, and intrusive and extrusive forces of 2 N were applied in random order to the experimental tooth for 5 min before unloading. The contralateral tooth se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 13 publications
3
9
0
Order By: Relevance
“…Reduced values of BFS were observed immediately after the forces were applied (20 minutes later), in accordance with other reports [5, 79]. Reduced values of BFS were also observed at 48 hours and 72 hours, in accordance with the results obtained by Sano et al [8].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Reduced values of BFS were observed immediately after the forces were applied (20 minutes later), in accordance with other reports [5, 79]. Reduced values of BFS were also observed at 48 hours and 72 hours, in accordance with the results obtained by Sano et al [8].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the technique has been used to evaluate alterations in blood flow in the dental pulp during orthodontic movements in humans. The information in the literature is limited to experimental movements such as intrusive (intermittent forces) [58], extrusive (intermittent forces) [5], intrusive (continuous forces during six days) [8], and tipping (continuous forces during three days) ones [9]. In these studies, experiments were carried out in laboratory, and the movements were monitored during short time intervals.…”
Section: Introductionmentioning
confidence: 99%
“…That said, all of these electric stimulus studies suggest a tendency for pulp recovery over time during orthodontic treatment. In accordance with the observations reported by other investigators [18,36,56], possible pulp sensitivity changes were measured almost immediately after an orthodontic load was applied. An electric pulp tester unit increment response threshold tendency was observed after the nickel titanium was applied.…”
Section: Discussionsupporting
confidence: 86%
“…Higher levels of inflammatory mediators have been likewise identified in pulp tissues and in gingival crevicular fluid during orthodontic treatment [16,[32][33][34]. However, other research groups [35,36] reported no significant effect of orthodontic intrusive and/ or extrusive forces on pulpal blood flow. In addition, Consolaro and Bianco Consolaro [37] claim that while light to moderate orthodontic forces applied to the periodontal ligament will promote periodontal cellular stress, which may evolve into a mild inflammation for some hours or days, they will recede in 2 to 7 days allowing periodontal reorganization between 10 and 15 days after the activation of orthodontic attachments.…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with several other authors ( Nixon et al, 1993 ; Raiden et al, 1998 ; Sano et al, 2002 ; Shigehara, Matsuzaka & Inoue, 2006 ; Wong et al, 1999 ). A drawback of the chosen measurement protocol in which the first histological evaluation is performed after one week is that short-lasting changes in the pulpal tissue, as described in the literature will be missed ( Barwick & Ramsay, 1996 ; Bletsa, Berggreen & Brudvik, 2006 ; Brodin, Linge & Aars, 1996 ; Ikawa et al, 2001 ; Nixon et al, 1993 ; Santamaria et al, 2007 ; Santamaria et al, 2006 ). However, this is not a serious problem as short-lasting pulpal changes are of less clinical importance than persisting ones.…”
Section: Discussionmentioning
confidence: 99%